Bonding behavior of CFRP grid-concrete with PCM shotcrete. (1st August 2018) - Guo, Rui; Pan, Yi; Cai, Lianheng; Hino, Shinichi
Highlights: The tensile force is transmitted through grid points and act on to PCM and concrete. The bonding behavior is better in specimens with additional adjacent axial grids. The essential number of grid points increases with the reduction of grid interval. Abstract: This study reveals the bonding behavior and stress transfer mechanism of a carbon-fiber-reinforced-polymer (CFRP) grid with polymer-cement-mortar (PCM) shotcrete on reinforced concrete (RC) members. The influence of the number of CFRP grid points, the interval of the horizontal grid, the existence of a vertical grid and the type of PCM on the bonding behavior of CFRP grid concrete with the PCM shotcrete method are discussed. The test results indicate that the tensile force transmits to the CFRP grid using the vertical grid points in turn, acting on the concrete via the PCM. Meanwhile, the horizontal grids provide the mechanical occlusal effect in this process. Once the transmitted tensile stress exceeds the ultimate bonding stress between concrete and PCM, peeling damage will occur. In addition, the deformation followability of the low-elasticity PCM was better than that of the high-strength PCM. This study also determines the essential number of grid points when the bonding behavior of the CFRP grid concrete with the PCM shotcrete is sufficient.